(untitled) (International Seven Journal of Health Research, 2023)
Introduction: The inadequate use of Personal Protective Equipment (PPE), as well as the absence of work accident prevention habits by waste collection agents, cleaning and conservation of urban areas can directly impact the health and safety indexes of workers. Objective: The present work aimed to investigate how the use of Personal Protective Equipment (PPE) and the habits of prevention of accidents at work adopted by agents of waste collection and cleaning and conservation of urban areas. Methodology: Quantitative, exploratory and descriptive research was carried out with a sample of 10 workers (8 direct collectors and 2 drivers) from the municipality of Nanuque-MG, the research sought to identify which PPE are provided to these professionals and the reasons why they possibly do not use them properly. Through literature review and application of questionnaires, it was possible to obtain information on the safety practices adopted and identify the role that employers should play for the safety of workers. Results: It was observed that 20% of workers claim to have already suffered an accident at work, of these 90% say that the employer distributed PPE. Of those interviewed, 10% say they have already suffered an accident with removal from the current job, the same percentage that confirms having already suffered a mild intercurrence and did not communicate to the employer. When asked if the company offered some kind of training, 50% say yes, 50% say no. Conclusion: The results revealed that the inadequate use of PPE is influenced by several factors, such as discomfort and lack of training.